An SFL Analysis of Interpersonal Metafunction in Constructing President Prabowo's Moral Authority at the UNGA - Rafiq al indra; Nur Aisyah Zulkifli (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study presents an SFL (Systemic Functional Linguistics) analysis of the Interpersonal Metafunction in President Prabowo's UNGA speech, focusing on the Mood and Modality systems to uncover the rhetorical strategies used in constructing his moral authority and negotiating Indonesia's role as a committed global actor. The analysis finds that while the Declarative Mood dominates to establish credibility, strategic shifts to the Interrogative Mood and the inclusive Imperative Mood ("We must...") are employed to actively engage the audience, demand moral reflection, and construct an accountable solidarity. The most significant finding is the dominance of High Value Modality, particularly the high frequency of High Deontic Modality ("must"), which linguistically elevates propositions such as the Two-State Solution to non-negotiable moral and political mandates. This choice is further reinforced by High Value Capacity/Willingness Modality, asserting Indonesia's credibility and agency. Overall, this sophisticated interpersonal strategy successfully positions President Prabowo as an authoritative and highly moral leader, linguistically imposing the highest level of conviction and demand for action upon the international community.